Establishment of the Accident Compensation Commission 1973: Administrative Challenges - Martin, John R (Victoria University of Wellington Law Review, 2003)
Alongside the process of legislative review and enactment, questions of administrative structure and implementation received lively consideration. At stake were such issues as whether to treat the new scheme as a matter of law reform or an aspect of social security. ACC’s eventual status as an independent commission posed challenges to public officials from several departments, while preserving certain tensions that would emerge later in the 1970s. This paper credits the New Zealand public service for its creative response to implementing ACC, which required it to bridge the structural divides and alternative conceptions of how the new scheme might work. The paper describes the pivotal decisions and persons that guided ACC into its initial decade.